Augmented reality in teaching and learning English reading: realities, possibilities, and limitations - Mohamed Jamrus, Mohd Hafizuddin; Mohamed Razali, Abu Bakar (Human Resource Management Academic Research Society, 2019)
Mobile technology that has recently taken its flight into emergence is called Augmented Reality. Advancements of AR have largely incorporated its uses through mobile technology, which makes it possible for just about anyone who has a mobile device to use AR such as can be seen in the widespread popularity of the online mobile games. Although augmented reality is still in the beginning stages of making its way into the educational realm, it does offer the capabilities of greatly enhancing our educational system. In fact, based on previous scholarly studies, Augmented Reality has been shown to be effective in learning the English language and could improve student motivation. This conceptual paper thus reports on past studies on the use and usefulness of Augmented Reality in teaching and learning in English language reading. In this paper, the concept of Augmented Reality, its usage in language learning, the benefits of using AR in language learning, the limitations in using AR in language learning, and teacher’s level of readiness and acceptance in using AR in classroom reading instruction will be discussed. The authors will also provide some recommendations for stakeholders, especially in regards to the use of Augmented Reality in teaching of English language reading, and also suggestions for future research.